Acute Hemoptysis Redefined: A Deadly Presentation - Claudio Galvis; Juan M. Galvis; Juan Guardiola; Adrian P. Umpierrez De Reguero (Case Reports in Pulmonology)
An aortic aneurysm is a permanent localized arterial dilation with more than 50% of the artery diameter. Among the complications of an aortic aneurysm, one of the rarest is the aorto-bronchial fistula, which presents with massive hemoptysis; this condition is lethal if not treated surgically. We report a 90-year-old man with no significant medical history who presented to the emergency department with abrupt onset of hemoptysis; his chest X-ray displayed left upper lobe opacity with widened mediastinum. CT chest revealed aneurysmatic dilatation of the aorta, left upper lobe opacity suspicious of pulmonary aortic fistula. Thoracic surgery was consulted but due to his poor functional status surgery was deferred. On the second day of hospitalization, the patient developed another episode of massive hemoptysis resulting in hypovolemic shock and expired. This case epitomizes the relevance of broad differential diagnosis for hemoptysis and the prompt assessment and management of the patients with this condition.